Berenstain Bears (The): and too much pressure - Berenstain, Stan (New York: Random House, 1992)
Members of the Bear family commit themselves to so many time-consuming activities that the resulting stress brings on a crisis and make them admit that there are only so many hours in a day.
Keywords: Time--Fiction.; Stress (Psychology)--Fiction.